2 x − 4 6 x 3 − 8 x − 5
What is the remainder of the expression above?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The fraction can be rewritten as 2 x − 4 ( 3 x 2 + 6 x + 8 ) ( 2 x − 4 ) + 2 7 = 2 x − 4 ( 3 x 2 + 6 x + 8 ) ( 2 x − 4 ) + 2 x − 4 2 7 which the remainder is 2 7 .
I was wondering: how did you come up with that rewriting of the numerator with the 2 7 that better clarifies what the remainder is? It seems like this is a case of solution based on already knowing what the answer is.
@Pi Han Goh - Do you know how to make a slash to cross out the two (2x-4)s? I'm not that good with latex but I know you are.
Log in to reply
Like this:
2 x − 4 ( 3 x 2 + 6 x + 8 ) ( 2 x − 4 ) + 2 7 = 2 x − 4 ( 3 x 2 + 6 x + 8 ) ( 2 x − 4 ) + 2 x − 4 2 7
OR
2 x − 4 ( 3 x 2 + 6 x + 8 ) ( 2 x − 4 ) + 2 7 = 2 x − 4 ( 3 x 2 + 6 x + 8 ) ( 2 x − 4 ) + 2 x − 4 2 7
OR
2 x − 4 ( 3 x 2 + 6 x + 8 ) ( 2 x − 4 ) + 2 7 = 2 x − 4 ( 3 x 2 + 6 x + 8 ) ( 2 x − 4 ) + 2 x − 4 2 7
ahh I see thank you @Pi Han Goh !
Problem Loading...
Note Loading...
Set Loading...
Let f ( x ) = 6 x 3 − 8 x − 5 and g ( x ) = 2 x − 4 . By remainder theorem the remainder of g ( x ) f ( x ) is f ( c ) , where c is the root of g ( x ) = 0 . Therefore, we have g ( x ) = 0 ⟹ 2 c − 4 = 0 ⟹ c = 2 . The remainder of g ( x ) f ( x ) is f ( c ) = f ( 2 ) = 6 ( 2 3 ) − 8 ( 2 ) − 5 = 2 7 .